2022
DOI: 10.1002/jclp.23415
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral students' intention to use assessments in their career: The incremental role of self‐reported competence

Abstract: Objective Attaining competence in assessment is a necessary step in graduate training and has been defined to include multiple domains of training relevant to this attainment. While important to ensure trainees meet these standards of training, it is critical to understand how and if competence shapes a trainees' professional identity, therein promoting lifelong competency. Methods The current study assessed currently enrolled graduate trainees' knowledge and perception of their capabilities related to assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Importantly, this study also assessed perceived competencies and related training needs. While perceived competency is an important and relevant metric, recent work has found that perceived competency is only weakly associated with performance‐based competency, suggesting a need for metrics which assess a scope of competency beyond self‐perceptions (Bergquist et al, 2023). Additionally, this study did not assess the quality of training strategies more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study also assessed perceived competencies and related training needs. While perceived competency is an important and relevant metric, recent work has found that perceived competency is only weakly associated with performance‐based competency, suggesting a need for metrics which assess a scope of competency beyond self‐perceptions (Bergquist et al, 2023). Additionally, this study did not assess the quality of training strategies more broadly.…”
Section: Discussionmentioning
confidence: 99%